Evolution of the galaxy stellar mass functions and UV luminosity functions at z = 6−9 in the Hubble Frontier Fields. Issue 3 (27th March 2019) - Bhatawdekar, Rachana; Conselice, Christopher J; Margalef-Bentabol, Berta; Duncan, Kenneth
Abstract: We present new measurements of the evolution of the galaxy stellar mass functions (GSMFs) and ultraviolet luminosity functions (UV LFs) for galaxies from z = 6−9 within the Frontier Field cluster MACSJ0416.1−2403 and its parallel field. To obtain these results, we derive the stellar masses of our sample by fitting synthetic stellar population models to their observed spectral energy distribution with the inclusion of nebular emission lines. This is the deepest and farthest in distance mass function measured to date and probes down to a level of M * = 10 6.8 M⊙ . The main result of this study is that the low-mass end of our GSMF to these limits and redshifts appears to become steeper from -1.98_-0.07^+0.07 at z = 6 to -2.38_-0.88^+0.72 at z = 9, steeper than previously observed mass functions at slightly lower redshifts, and we find no evidence of turnover in the mass range probed. We furthermore demonstrate that the UV LF for these systems also appears to show a steepening at the highest redshifts, without any evidence of turnover in the luminosity range probed. Our M UV − M * relation exhibit shallower slopes than previously observed and are in accordance with a constant mass-to-light ratio. Integrating our GSMF, we find that the stellar mass density increases by a factor of 15_-6^+21 from z = 9 to z = 6. We estimate the dust-corrected star formation rates (SFRs) to calculate the specific SFRs (sSFR = SFR/ M * ) of our sample, and find that for a fixed stellar mass of 5 × 10 9 M⊙, sSFR ∝ (1 + z ) 2.01 ± 0.16 . Finally, from our new measurements, we estimate the UV luminosity density (ρUV ) and find that our results support a smooth decline of ρUV towards high redshifts.